Implementasi Pembelajaran Daring bagi Prodi Pendidikan Agama Islam Universitas Ahmad Dahlan Selama Pandemi COVID-19 di Indonesia - Nurfajriyah Azani (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
The purpose of this research is to recognize the implementation of online learning in the Islamic Religious Education study program at Ahmad Dahlan University during the COVID-19 pandemic in Indonesia. This research is a descriptive field study with qualitative data, this study aims to examine the implementation of online learning. Researchers used primary data sources in the form of interviews and observations and secondary data sources from the documentation. Methods of data collection using the method of observation, interview methods, and methods of documentation. Observation method to observe the phenomenon of online learning implementation. The interview method was carried out to lecturers and students of the Islamic Religious Education study program. Documentation method for documenting everything related to online learning. The data validity was done by using triangulation techniques, cross-checking between the results of observations, the results of interviews, and the method of documentation. The results of the study stated that online learning in the Islamic Religious Education study program uses the google meet application, google classroom, zoom, e-learning, and WhatsApp. This study describes the supporting and inhibiting factors, the supporters are taking advantage of time, technological literacy, practicality, and understanding of the student's condition, while the inhibiting factors are network, time, facilities, media, and seriousness towards online learning.